2003
DOI: 10.1046/j.1523-1747.2003.12470.x
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Molecular Organization of Multilamellar Emulsions Containing Pseudoceramide and Type III Synthetic Ceramide

Abstract: To investigate the molecular organization and phase behavior of physiologic lipid mixtures that contain either newly synthesized pseudoceramide or type III synthetic ceramide, various analytical techniques were used. The phase transition temperatures detected in differential scanning calorimetry analysis were 51.19 and 50.52 for the pseudoceramide-containing physiologic lipid mixture and synthetic type III ceramide-containing lipid mixture, respectively. From the small angle XRD patterns, the multilamellar emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Sphingolipids, especially ceramide, are the major components of the intercellular materials in the stratum corneum, and a decrease in some of these molecules may be the cause of several skin diseases related to abnormal keratinocyte differentiation (24). We have studied synthetic ceramides and the multilamellar emulsion expected to reconstitute the abnormal skin barrier that results from the decrease in ceramide biosynthesis, such as in atopic dermatitis and psoriasis, and the barrier impairment induced by glucocorticoid-epidermal atrophy (15)(16)(17)(18). Here, we studied another possible use of these synthetic ceramides: as a bioactive lipid mediator of keratinocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids, especially ceramide, are the major components of the intercellular materials in the stratum corneum, and a decrease in some of these molecules may be the cause of several skin diseases related to abnormal keratinocyte differentiation (24). We have studied synthetic ceramides and the multilamellar emulsion expected to reconstitute the abnormal skin barrier that results from the decrease in ceramide biosynthesis, such as in atopic dermatitis and psoriasis, and the barrier impairment induced by glucocorticoid-epidermal atrophy (15)(16)(17)(18). Here, we studied another possible use of these synthetic ceramides: as a bioactive lipid mediator of keratinocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we developed the synthetic ceramide PC-9S (N-(2,3-dihydroxypropyl)-2-hexyl-3-oxo-decanamide) and reported its effects on skin barrier function (15)(16)(17)(18). During those studies, we postulated that PC-9S also has a biological effect on epidermal differentiation.…”
mentioning
confidence: 99%
“…For example, when present as the dominant species in a 3:1:1 molar ratio, they accelerate barrier recovery after acute abrogation in comparison to vehicletreated sites [4,14]. Two pseudo-Cer, i.e., N-(3-hexadecyloxy-2-hydroxypropyl)-N-2-hydroxyethylhexadecanamide (PC-104) and a similar structural compound, N-(2-hydroxyethyl)-2-pentadecanolylhexadecanamide (Bio391), can form lamellar/multilamellar structures in vitro with cholesterol and free fatty acids [15][16][17]. Accordingly, the cutaneous symptoms of atopic dermatitis appear to improve in patients treated with pseudo-Cer (PC-104 and others)-containing mixtures [4,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the roles in skin barrier function, ceramide also regulates a variety of cellular processes, including cell growth, differentiation, apoptosis, inflammation and immune responses [10,11]. We previously developed a synthetic ceramide, PC-9S, and showed that it has a protective effect on skin barrier function [12][13][14][15]. Clinical efficacy of PC-9S on atopic or psoriatic patients was also reported [12,14,16].…”
Section: Introductionmentioning
confidence: 99%